Portrait of attendees at the Pacific Division convention for the Amateur Radio League - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the American Radio Relay League Pacific Convention in front of the San Jose Civic Auditorium. The convention was hosted by the Santa Clara Co. Amateur Radio Association and held July 3-5, 1954 in San Jose, California.